PENGELOMPOKAN JUMLAH PENDUDUK BERDASARKAN KATEGORI USIA DENGAN METODE K-MEANS - Sahat Sonang; Arifin Tua Purba; Ferri Ojak Imanuel Pardede (Politeknik Bisnis Indonesia, 2019)
Control of population is one of the tasks of the government in Indonesia. The increase and movement of population in each region makes a certain area to defeat changes in population surging, and this can affect the economic level of the area. This study aims to process the population of Pematangsiantar City in 2018 which is divided into age groups, namely: Toddlers, Young Children, Early Adolescents, Late Adolescents, Early Adolescents, Late Adulthood, Early Adulthood, Elderly, Late Elderly, and Upper Seniors. Data processing is done by using K-Means method clustering in accordance with the population of Pematangsiantar City per district. With this grouping, we can see that the number of population in each sub-district is based on each age group so that we can implement programs that are more appropriate in improving human resources.